2013
DOI: 10.1093/nar/gkt327
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor induces bcl-x expression through intragenic binding sites favoring RNA polymerase II elongation

Abstract: Steroid receptors were classically described for regulating transcription by binding to target gene promoters. However, genome-wide studies reveal that steroid receptors-binding sites are mainly located at intragenic regions. To determine the role of these sites, we examined the effect of progestins on the transcription of the bcl-x gene, where only intragenic progesterone receptor-binding sites (PRbs) were identified. We found that in response to hormone treatment, the PR is recruited to these sites along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…To better elucidate the molecular mechanisms by which P4-activated PRA regulated BCL 2- L 1 gene expression in MDA-iPRA cells and based on previous studies performed in T47D cells [ 27 ], ChIP assays were performed to examine PRA recruitment on one genomic target motif, already established on BCL 2 -L 1 gene [ 31 ]. We chose the intragenic PR-binding sequence located at +58 kb downstream Transcription Start Site (TSS) of BCL 2 -L 1 gene as schematically depicted in the genomic structure of the human BCL 2 -L 1 gene ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…To better elucidate the molecular mechanisms by which P4-activated PRA regulated BCL 2- L 1 gene expression in MDA-iPRA cells and based on previous studies performed in T47D cells [ 27 ], ChIP assays were performed to examine PRA recruitment on one genomic target motif, already established on BCL 2 -L 1 gene [ 31 ]. We chose the intragenic PR-binding sequence located at +58 kb downstream Transcription Start Site (TSS) of BCL 2 -L 1 gene as schematically depicted in the genomic structure of the human BCL 2 -L 1 gene ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP was performed as published (5). Library preparation and sequencing were carried out following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, amid an avalanche of papers reporting various connections between the chromatin context and splicing (3)(4)(5)(6)(7)(8)(9), a relationship between splicing and small RNAs has emerged. The convergence of these previously unrelated areas (RNA interference, chromatin, and splicing) has been studied by our laboratory, showing that siRNAs (20-25 nt long) targeting both intronic and exonic regions near the cassette exon 33 (E33, also known as EDI) of the fibronectin gene were able to regulate its alternative splicing by affecting the chromatin context at the target region, with an increase of histone tail modifications associated with gene silencing (H3K9me2 and H3K27me3, i.e., dimethylation of lysine 9 and trimethylation of lysine 27 of histone H3 respectively).…”
mentioning
confidence: 99%
“…We have here reported that HRG␤1-activated Stat3 regulation on bcl-X transcription occurs via an intact PRE (Supplemental Figure 5A). Recently, ligand-activated PR was shown to regulate the transcription of human bcl-X by modulating the RNA polymerase II elongation process through binding to intragenic PREs (57). It remains to be determined whether unliganded PR exerts the latter regulation in the transcription of the murine bcl-X gene in spite of the divergence of the intronic sequences between both species.…”
Section: Discussionmentioning
confidence: 99%